LUMBA-LUMBA DALAM KARYA TAPESTRI - Efri Rahayu Pertiwi; Erwin Erwin (Serupa The Journal of Art Education, 2020)
The creation of this final work aims to visualize the style and behavior / movements of dolphins through tapestry works. The work displays the object of dolphins in a happy motion. Embodiment method of this work through stages, namely: preparation, elaboration, synthesis, concept realization, and completion. The author succeeded in realizing 7 works with the title: Helper, Leap, Hunt for prey, Togetherness, Compassion, Friendship, and Free.keywords: behavior, dolphin, tapestry